1999
DOI: 10.1021/bi990286o
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Substitutions of Lysine and Aspartic Acid for Asparagine at β108 and of Tryptophan for Valine at α96 on the Structural and Functional Properties of Human Normal Adult Hemoglobin:  Roles of α1β1 and α1β2 Subunit Interfaces in the Cooperative Oxygenation Process

Abstract: Using our Escherichia coli expression system, we have produced five mutant recombinant (r) hemoglobins (Hbs): r Hb (alpha V96 W), r Hb Presbyterian (beta N108K), r Hb Yoshizuka (beta N108D), r Hb (alpha V96W, beta N108K), and r Hb (alpha V96W, beta N108D). These r Hbs allow us to investigate the effect on the structure-function relationship of Hb of replacing beta 108Asn by either a positively charged Lys or a negatively charged Asp as well as the effect of replacing alpha 96Val by a bulky, nonpolar Trp. We ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
77
3

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(92 citation statements)
references
References 47 publications
12
77
3
Order By: Relevance
“…This result suggests that structural changes at the ␣ 1 ␤ 1 ͞␣ 2 ␤ 2 interfaces can propagate to the ␣ 1 ␤ 2 ͞␣ 2 ␤ 1 interfaces and thus can affect the allosteric equilibrium. Support for this suggestion has been provided by Ho and coworkers, who found that Asn␤108(G10) 3 Lys and Asn␤108(G10) 3 Glu substitutions at the ␣ 1 ␤ 1 ͞␣ 2 ␤ 2 interfaces favor the T state relative to the R state, at low temperature and in the presence of allosteric effectors (24). Moreover, these two amino acid substitutions have been shown to have profound effects on the Bohr effect and on the linkage between oxygen and chloride ions (24).…”
Section: Allosteric Free Energy Changes At His␣103(g10) and His␣122(hmentioning
confidence: 80%
See 2 more Smart Citations
“…This result suggests that structural changes at the ␣ 1 ␤ 1 ͞␣ 2 ␤ 2 interfaces can propagate to the ␣ 1 ␤ 2 ͞␣ 2 ␤ 1 interfaces and thus can affect the allosteric equilibrium. Support for this suggestion has been provided by Ho and coworkers, who found that Asn␤108(G10) 3 Lys and Asn␤108(G10) 3 Glu substitutions at the ␣ 1 ␤ 1 ͞␣ 2 ␤ 2 interfaces favor the T state relative to the R state, at low temperature and in the presence of allosteric effectors (24). Moreover, these two amino acid substitutions have been shown to have profound effects on the Bohr effect and on the linkage between oxygen and chloride ions (24).…”
Section: Allosteric Free Energy Changes At His␣103(g10) and His␣122(hmentioning
confidence: 80%
“…Support for this suggestion has been provided by Ho and coworkers, who found that Asn␤108(G10) 3 Lys and Asn␤108(G10) 3 Glu substitutions at the ␣ 1 ␤ 1 ͞␣ 2 ␤ 2 interfaces favor the T state relative to the R state, at low temperature and in the presence of allosteric effectors (24). Moreover, these two amino acid substitutions have been shown to have profound effects on the Bohr effect and on the linkage between oxygen and chloride ions (24). Therefore, it appears that the role of the ␣ 1 ␤ 1 ͞␣ 2 ␤ 2 interfaces in the Hb function is not negligible.…”
Section: Allosteric Free Energy Changes At His␣103(g10) and His␣122(hmentioning
confidence: 80%
See 1 more Smart Citation
“…Mutations of Asnb108 in the a 1 b 1 interface can result in lower oxygen affinity and normal cooperativity compared to HbA, indicating a role for this interface in the allosteric transition. 29,30 Also, mutation of Glnb131, the acceptor of an a 1 b 1 interface H-bond, perturbs another interfacial H-bond some 7 Å distance, possibly via a network of ordered water molecules. Hydrogen exchange of the histidine residues involved in these H-bonds differs significantly between CO-and deoxyHb.…”
Section: Intra-and Interdimer Dynamicsmentioning
confidence: 99%
“…8 the Perutz salt bridge model has accounted for a wide range of both structural and functional Hb properties, as long as the symmetry of the Hb tetramer was preserved and as long as the system was studied as the average of its ligation intermediates. Still, elements of the two-state model, which permits global quaternary rearrangement, but no sequential inter-subunit coupling, have frequently been questioned from a wide range of perspectives (9)(10)(11)(12)(13)(14)(15)(16). Systematic deviations from the two-state model become most apparent when the Hb system is resolved into its separate, partially ligated microstates, some of which are asymmetrically ligated (17)(18)(19)(20)(21).…”
mentioning
confidence: 99%